Phase 2 randomized controlled trial of intravenous or intraperitoneal paclitaxel plus mFOLFOX6 vs. mFOLFOX6 as first-line treatment of advanced gastric cancer - Zhao, Shen; Su, Liyu; Chen, Yigui; Li, Xiaofeng; Lin, Peicheng; Chen, Wujin; Fang, Wenzheng; Zhu, Jinfeng; Li, Hui; Ren, Liping; Liu, Jie; Hong, Yanni; et al. (Frontiers in Oncology, 2022)
Objective: We conducted a phase 2 trial to compare the safety and efficacy of intravenous paclitaxel or intraperitoneal paclitaxel plus mFOLFOX6 vs. mFOLFOX6 in untreated advanced gastric cancer. Methods: Participants with untreated advanced gastric cancer were randomly assigned (1:1:1) to: intravenous paclitaxel 135 mg/m2 or intraperitoneal paclitaxel 80 mg/m2 plus mFOLFOX6 omitting bolus fluorouracil; or mFOLFOX6 (oxaliplatin 85 mg/m2, leucovorin 400 mg/m2, fluorouracil 400 mg/m2 bolus, fluorouracil 2400 mg/m2 46-hour continuous infusion). Treatment was every 14 days for up to 9 cycles followed by S-1 maintenance. The primary outcome was progression-free survival. Results: Of 90 enrolled participants, 30 in the intravenous paclitaxel group, 29 in the intraperitoneal paclitaxel group, and 30 in the mFOLFOX6 group were included in analyses. Median progression-free survival was 6.52, 5.83, and 4.55 months, respectively, for intravenous paclitaxel group, intraperitoneal paclitaxel group, and mFOLFOX6 group. Hazard ratios were 0.56 (95% CI: 0.33-0.94; P=0.026); 0.56 (95% CI: 0.33-0.96; P=0.037), respectively, for intravenous paclitaxel group and intraperitoneal paclitaxel group versus mFOLFOX6 group. The most common grade 3/4 adverse events for intravenous paclitaxel group, intraperitoneal paclitaxel group, and mFOLFOX6 group, respectively, were: neutropenia (30.0%, 34.5%, 33.3%); diarrhea (13.3%, 20.7%, 13.3%); and leukopenia (10.0%, 13.8%, 10.0%). No treatment-related death occurred. Conclusion: The findings of this phase 2 trial suggest that adding intravenous paclitaxel or intraperitoneal paclitaxel to mFOLFOX6 for untreated advanced gastric cancer improved progression-free survival with manageable adverse events.